1979
DOI: 10.1038/bjc.1979.1
|View full text |Cite
|
Sign up to set email alerts
|

Breast-cancer incidence and mortality rates in different countries in relation to known risk factors and dietary practices

Abstract: Summary.-Breast-cancer incidence and mortality rates in different countries were found to be correlated with height, weight and age at menarche, all of which have been identified as risk factors in cohort or case-control studies of breast cancer. There were, however, correlations with total fat and animal protein consumption per capita even after controlling for the 3 anthropometric variables. This suggests that, while some of the effects of diet on breast-cancer rates may be mediated through effects on these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1
1

Year Published

1983
1983
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(39 citation statements)
references
References 19 publications
2
35
1
1
Order By: Relevance
“…Breast cancer is the most common cancer among women in the Western world and the second leading cause of cancer-related deaths in women (2,3). Several cancers, including breast cancer, have a lower incidence in Asia than in Western countries (77). This may be attributed to the typical Asian dietary regimens which are rich in flavonoid-containing plants, and which are thought to be anti-tumorigenic.…”
Section: Apigenin and Cancermentioning
confidence: 99%
“…Breast cancer is the most common cancer among women in the Western world and the second leading cause of cancer-related deaths in women (2,3). Several cancers, including breast cancer, have a lower incidence in Asia than in Western countries (77). This may be attributed to the typical Asian dietary regimens which are rich in flavonoid-containing plants, and which are thought to be anti-tumorigenic.…”
Section: Apigenin and Cancermentioning
confidence: 99%
“…Epidemiologic studies suggest that the increased consumption of soy products by Asian women contributes to lower breast cancer incidence and mortality rates compared with women from industrialized Western nations (17)(18)(19). The protective effects of soy-based diets may be related to the high levels of naturally occurring hormone-like isoflavones found in soybeans (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have shown wide geographical variations in the occurrence of breast cancer in women (Miller, 1977;Gray et al, 1979). Asian women who consume traditional soy products have much lower incidence and mortality of breast cancer.…”
Section: Introductionmentioning
confidence: 99%